경북 문화콘텐츠산업의 현황과 육성 방향 - 서곡숙(Kok-Suk Seo) (한국콘텐츠학회 논문지, 9(5), 2009)
Culture contents industry in Gyeongbuk province has consumption system, being small-scale, an lacking infrastructure, imbalance, a shortage of strategy, and so on. But, culture contents industry in Gyeongbuk province has great possibilities in abundant culture resources, a prospect of the culture contents industry and future effective promotion strategy. And the promotion plans are the digitalization of the cultural original form, the edutainment of the Confucianism culture, construction of a traditional cultural digital center, location marketing, establishment of Documentary Film Council, culture literacy, an orientation of small film, promotion of the global city and the culture base city, development of killer contents, exploitation of tourism resource, discriminating strategy, and so on. Actually Gyeongbuk province should need to promote the culture contents industry because of high added value, an effect on related industries, utility of the digital culture contents, extension of a market scale, a rapid growth speed, and so on. 경북 문화콘텐츠산업은 소비지향적 구조, 영세성, 부족한 인프라, 불균형, 전략 부재 등의 문제점을 안고 있다. 하지만, 경북 문화콘텐츠산업은 풍부한 문화자원, 문화콘텐츠산업의 전망, 미래의 효과적인 육성전략으로 인해서 그 가능성이 크다고 할 수 있다. 그리고 육성방안으로는 문화원형의 디지털화, 유교 문화의 에듀테인먼트, 전통문화디지털센터의 구축, 장소마케팅, 다큐영상원 건립, 문화 리터러시, 작은 영상 지향, 글로벌 도시와 문화거점 도시의 육성, 킬러 콘텐츠 개발, 관광자원 개발, 차별화 전략 등이 있다. 문화콘텐츠산업은 고부가가치, 관련 산업에 대한 영향력, 디지털문화콘텐츠의 효용성, 시장 규모의 확대, 빠른 성장속도 등의 측면에서 경북도 문화콘텐츠산업을 적극적으로 육성해야 할 필요성이 있다.